Stability of versions of the Weyl-type theorems under tensor product - Prasad, T.; Rashid, M. H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the transformation versions of the Weyl-type theorems from operators $T$ and $S$ for their tensor product $T \otimes S$ in the infinite-dimensional space setting.